Remote introductory pharmacy practice experiences focused on veterans prescribed chronic opioid therapy. (23rd December 2020) - Carr-Lopez, Sian M; Strohecker, Lorrie; Miyahara, Randell; Mai, Yvonne; Shek, Allen
Abstract: Purpose: The Department of Veterans Affairs (VA) Northern California Health Care System (NCHCS) uses a dashboard to identify monitoring needs for veterans prescribed chronic opioid therapy (COT). Schools of pharmacy require introductory pharmacy practice experiences (IPPEs); however, resources for providing IPPEs at medical facilities are limited. This article describes collaboration by a primary care service and a school of pharmacy to provide services for patients prescribed COT through remote access to the VA electronic health record (EHR) system. Summary: Pharmacy students in a required population health IPPE provided clinical services for veterans remotely. Students were supervised by VA clinical pharmacists and granted remote EHR access privileges. Using personally owned laptops and VA cell phones, students performed prescription drug monitoring program (PDMP) activities, reviewed urine drug screening (UDS) results, called patients to assess pain, and documented progress notes. Students completed an assessment on the first and final days of the experience; a retrospective analysis was conducted to examine differences in student knowledge of and confidence in providing COT-focused services. The dashboard scorecard and student workload were tracked over a 1-year period. In that year, 143 students wrote 7, 001 PDMP notes, reviewed 6, 130 UDS results, and documented 202 pain assessments. Statistically significant improvements were reported in students' level of confidence in performing population health activities for patients prescribed COT, including interpreting PDMP and UDS results and talking with patients. Conclusion: The ongoing collaboration provides real-world population management experiences for future pharmacists and supports monitoring requirements for veterans prescribed COT. The program has helped NCHCS accomplish its teaching mission without dedicating clinic workspace or computers and gain an additional team to address quality measures and support population health activities.